A dual‐function switchable and frequency tunable active frequency selective surface. Issue 12 (20th September 2021) - Liang, Yulin; Chen, Mingsong; Peng, Lin; Li, Zihan
Abstract: A dual‐function switchable and frequency tunable active frequency selective surface (AFSS) is proposed in this article. The proposed AFSS consists of a dielectric substrate and metal patches on the top and bottom surfaces of the substrate, while varactor diodes and PIN diodes are soldered on the top and bottom layers, respectively. A simple bias network is designed to facilitate the function adjustment of the AFSS. By controlling the OFF and ON states of the PIN diode, the AFSS can switch between filtering and wave absorbing functions. Furthermore, by adjusting the bias voltage of the top varactor diode, the AFSS can achieve continuous frequency tunability. Simulation and experimental results confirm the dual‐function switchable and frequency tunable performance of the proposed AFSS.